INVENTORY AND CHARACTERIZATION OF EROSIVE FORMS IN THE BARBANTIÑO RIVER (MIÑO BASIN, GALICIA, NW PENÍNSULA IBÉRICA) - Elena de Uña-Álvarez; Miguel Ángel Álvarez-Vázquez; Maria Luz Rodríguez-Blanco; Alexandra Maria Ramírez-Pérez (Environmental Smoke, 2021)
The existence of forms sculpted by fluvial erosion is frequent in Bedrock Rivers. Since 1999, the Area of Physical Geography of the University of Vigo (Ourense Campus) has been conducting research on these rock cavities in various reaches of the middle Miño River. The exploratory study that is presented corresponds to the case of a section upstream of the Barbantiño river waterfall (Ourense, Galicia). Carried out within the framework of a research line with the objectives of inventorying, characterizing, interpreting and evaluating the erosive forms in the rocky channels of the Miño River and its tributaries, the employed methodology included phases of field work, creation of a database, and statistical analysis. From the records in the sampled sectors of the Barbantiño River, an inventory was made with 60 erosive forms, considering quantitative variables (measurements of length, width, depth) and qualitative variables (morphology of the bottom, state of the walls, and presence of deposits). The preliminary results of the exploratory analysis provide new information on the sculpted forms in bedrock, allowing comparison with previous studies. The erosive forms of the studied section are characterized by great variability in their depth (between 2 cm and 2.7 m), length (between 7 cm and 2.5 m) and width (between 4 cm and 2 m); the strong correlation between surface and bottom dimensions (Spearman's r> 0.85); and the coexistence of cavities in an incipient state, furrows and potholes. These results contribute to the advancement of knowledge of a natural legacy that is part of the geodiversity of the Miño River basin, with a complex of values associated with its condition of geomorphological heritage.